THE RESISTANCE ASPECT OF FISHING BOAT SKIPJACK POLE AND LINE - Wolter R Hetharia; Eliza R de Fretes; Reico H Siahainenia (Fakultas Teknik Universitas Pattimura, 2021)
The operation of fishing vessels skipjack pole and line contributes in catching tuna and skipjack fishes particularly in Indonesian waters. A previous study conducted by the authors found that there was no suitable method provided for the resistance computation atearly ship design phase. Besides, there was aninitial trim existed on the vessel during the operation which contributes for the resistance. The purpose of the study is to find the difference of resistance between the model test and the existing methods. The study was executed also to find the effect of initial trim of the vessel. The study began with collecting the database of a parent ship then to develop and transform into a model-scale for testing purpose in the towing tank. The results of model test were converted to the full-scale vessel. The resistance of full-scale vessel was computed based on the Holtrop and Guldhammer methods. The result of full-of resistance obtained from the model test and the methods were collected, evaluated and compared. The results showed the difference of the resistance for all methods. The result of model test is greater 21 % than that of Holtrop method at the service speed of 10 knots. Meanwhile, the result of model test is lower 14 % than that of Gulhammer method at the same speed. In addition, at the speed of 10 knots the initial trim of 0.5O increase 5 % ofthe resistance, the initial trim of 1O increase 10 % of resistance and the initial trim of 2O increase 16 % of resistance compared to the vesselwithout initial trim. In conclusion, the existing resistance methods are not suitable to be applied for skipjack pole and line fishing vessels. In addition, the initial trim contributes to increase the resistance and should be avoided during the vessel operation.